TOXICITY EVALUATION OF AQUEOUS STEM EXTRACTS OF Euphobia lateriflora (SCHUM AND THONN) IN SOME ALBINO RATS - MAIKUDI USMAN , MOHAMMED; SANI SULE, MUHAMMAD (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The effect of administration of graduated dose of an aqueous stem extract of Euphorbia lateriflora on alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), bilirubin, total protein, creatinine and urea in rats were determined to ascertain the toxic effects on the liver and kidney. There was a significant increase (p< 0.05) in ALT activity and significant decreases in urea level in the group administered with 100mg/kg aqueous stem extract of Euphorbia lateriflora compared to the control. In groups administered with 250mg/kg, there was a significant increase (p < 0.05) in ALT, AST activities and bilirubin level than the control. The result suggests a possible hepatotoxic effect of root extract of Euphorbia lateriflora after administration of 100 mg/kg and 250 mg/kg. There was no possible kidney malfunction. The result of the oral acute toxicity study shown that Euphorbia lateriflora have oral LD50 above 5000 mg/kg.